Is lactate a volume transmitter of metabolic states of the brain? - Bergersen, Linda H.; Gjedde, Albert (Frontiers in Neuroenergetics, 2012)
We present the perspective that lactate is a volume transmitter of cellular signals in brain that acutely and chronically regulate the energy metabolism of large neuronal ensembles. From this perspective, we interpret recent evidence to mean that lactate transmission serves the maintenance of network metabolism by two different mechanisms, one by regulating the formation of cAMP via the lactate receptor GPR81, the other by adjusting the NADH/NAD+ redox ratios, both linked to the maintenance of brain energy turnover and possibly cerebral blood flow. The roles of lactate as mediator of metabolic information rather than metabolic substrate answer a number of questions raised by the controversial oxidativeness of astrocytic metabolism and its contribution to neuronal function.